Analisis Motif Batik Kembang Turi Sebagai Identitas Budaya Lokal Di Kampung Wisata Batik Turi Kota Blitar - Ni’amah, Ulva; Ratnawati, Ike (Jurnal Pendidikan dan Penciptaan Seni, 2025)
Batik is one of Indonesia’s cultural heritages that serves not only as a work of art but also as a regional identity symbol, representing values, history, and local wisdom. This study explores in depth the Kembang Turi batik motif as a symbol of the local culture of the community in Kelurahan Turi, Blitar City. The research aims to analyze the origin and development of the motif and to describe the form, meaning, and uniqueness of the Kembang Turi Batik motif. This research employs a descriptive qualitative method. Data collection techniques include observation, interviews, and documentation as supporting data. The results show that the Kembang Turi Batik motif, inspired by the natural shape of the turi flower, is enriched with supporting motifs that highlight the cultural potential of Blitar City. Since 2018, this motif has developed into a recognized symbol of local cultural identity, reflecting philosophical values such as simplicity, vitality, and the preservation of traditional arts. The motif also serves educational, aesthetic, and economic functions, supporting the strengthening of local identity and the promotion of regional culture.